Avaliação do uso de accruals discricionários: uma abordagem qualitativa quanto às práticas de auditoria e seu poder de mitigação - Leite, Rodrigo Romanato (2012)
The earnings management practices started to be researched more intensely, concerning international terms, after the corporate scandals occurred in the beginning of 2000 years In Brazil, this research topic has mainly focused the quantitative approaches (discretionary accruals evaluation and operational models discussion). The research that resulted the present work has highlighted, according to the statistical tests, that the companies audited by the Big Four have less degree of accruals discretionary regarding to the other companies audited by companies Non Big Four, then, showing that the largest audit companies have a larger capacity to mitigate earnings management. In the presented context, this work aimed to investigate which are the main factors that specify the higher power of the big audit companies (Big Four) in mitigating the earnings management practices. Also, it has being identified the tools used by the independent audit companies for the work performance process, which, among other aspects, could make easier the earnings management practices identification process. The research herein presented was performed using the qualitative method (exploratory by nature), and using as procedure the data collecting, heartfelt interview with eight audit professionals. The data collected were analyzed through content analysis, using the software NVIVO. In this research it was identified the main job differential factors of these companies: company insertion environment and abroad relationship, audit company structure, audit company exposure, audit tools, compliance with the independence rules, work methodology and audit procedures, auditors training and qualification. Also, it was noticed that the audit companies are able or not to use customized tools to perform the jobs, sampling extraction processes and results projection, being its utilization related to the audit company size.